ChemInform Abstract: Synthesis of Biologically Active Diazepam Derivatives. Issue 3 (22nd January 2013) - Kumar, S. Sathish; Kavitha, Helen P.; Arulmurugan, S.; Venkatraman, B. R.
Abstract Review: 133 refs.